Perancangan Sistem Pendukung Keputusan Penerimaan Siswa Baru Dengan Menerapkan Metode Composite Performance Index(cpi) (studi kasus: SDN 101864 Gunung Rintih) - Robertus Siahaan (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2021)
Decision support system is part of a computer-based information system that is commonly used to support decision making in an organization or company. Decision support systems can be generated using several methods, one of which is the Composite Performance Index (CPI) method. Composite Performance Index is a composite index that can be used to determine the determination or ranking of various alternatives based on several criteria. By using this Composite Performance Index, it is hoped that the process of admitting new students is more effective and efficient so that students quickly get information about whether or not the prospective student is accepted and the results are in accordance with the expected results.